Efeito do molibdênio substitucional na estrutura, microestrutura e algumas propriedades mecânicas de ligas do sistema Ti-20Zr-Mo - Kuroda, Pedro Akira Bazaglia [UNESP] (2015)
Titanium and alloys currently are used as implants possessing excellent corrosion resistance and mechanical properties more suited to stainless steel implants and Co-Cr. The titanium alloy used for most biomedical applications is Ti-6Al-4V, however studies showed that vanadium cause allergic reactions in human tissues and alluminum has been associated with neurological disorders. So to overcome this problem, new titanium alloys without the presence of these elements are being studied. The objective of this study is to anlyze the influence of molybdenum substitutional solute in the structure, microstructure, hardness and elastic modulus of ternary alloy Ti-20Zr-Mo system, where the molybdenum content was varied from 0,2,5,5,7,5 to 10% by weight. The chemical characterization of materials was performed by spectroscopy EDS, XRF, chemical mapping and density measurements...